Effect of Ethanol Extract of Basil Leaves (Ocimum basilicum) on the number of M2 Macrophages in the Kidneys of Mice (Mus musculus) Using the Unilateral Ureteral Obstruction (UUO) Method - Farhany, Muhammad Achya; Karita, Dewi; Maulana, Andi Muh.; Ratnaningsih, Mustika (Universitas Muhammadiyah Semarang, 2022)
Background: Chronic Kidney Disease (CKD) is a problem in nephrology with a fairly high incidence rate, the final condition of CKD is the presence of kidney fibrosis in the tubulointerstitial region depending on the polarization of macrophages. Basil antioxidant efficacious leaves can prevent damage to tubular cells in animals.Objective: To determine the effect of giving basil leaf extract (Ocimum basilicum L.) on the amount of M2 macrophages in mice (Mus musculus) with the Unilateral Ureteral Obstruction method.Methods: This research use an experimental study using a posttest only with randomized controlled group design.Results: Data on administration of basil leaf extract (Ocimum basilicum L.) to mice can reduce damage to the kidneys analyzed using LSD test obtained p value (0.000 <0.005). The amount of M2 macrophages in mice given basil ethanol extract with the largest dose was 24 mg /20grBW compared to the administration of basil ethanol extract at a dose of 12 mg/20grBW and 48mg/20grBW.Conclusion: Administration of basil leaves extract (Ocimum basilicum L. ) in mice can reduce damage to the kidneys.